ALA induces stomatal opening through regulation among PTPA, PP2AC, and SnRK2.6 - Chen, Zheng; Zhang, Jianting; Wang, Liangju (Frontiers in Plant Science, 2023)
5-Aminolevulinic acid (ALA), as a new natural plant growth regulator, has been proved to regulate protein phosphatase 2A (PP2A) activity to promote stomatal opening in apple (Malus domestica) leaves. However, the molecular mechanisms underlying remain unclear. Here, we cloned and transformed MdPTPA, MdPP2AC, and MdSnRK2.6 of apple into tobaccos (Nicotiana tabacum) and found that over-expression (OE)-MdPTPA or OE-MdPP2AC promoted stomatal aperture while OE-MdSnRK2.6 induced stomatal closure under normal or drought condition. The Ca2+ and H2O2 levels in the guard cells of OE-MdPTPA and OE-MdPP2AC was decreased but flavonols increased, and the results in OE-SnRK2.6 was contrary. Exogenous ALA stimulated PP2A activity but depressed SnRK2.6 activity in transgenic tobaccos, leading to less Ca2+, H2O2 and more flavonols in guard cells, and consequently stomatal opening. OE-MdPTPA improved stomatal opening and plant growth but impaired drought tolerance, while OE-MdSnRK2.6 improved drought tolerance but depressed the leaf Pn. Only OE-MdPP2AC improved stomatal opening, leaf Pn, plant growth, as well as drought tolerance. These suggest that the three genes involved in ALA-regulating stomatal movement have their respective unique biological functions. Yeast two-hybrid (Y2H) assays showed that MdPP2AC interacted with MdPTPA or MdSnRK2.6, respectively, but no interaction of MdPTPA with MdSnRK2.6 was found. Yeast three-hybrid (Y3H) assay showed that MdPTPA promoted the interactions between MdPP2AC and MdSnRK2.6. Therefore, we propose a regulatory module of PTPA-PP2AC-SnRK2.6 that may be involved in mediating the ALA-inducing stomatal aperture in green plants.